Pengaruh Model PBLdan Keterampilan Berpikir Kritis Terhadap Hasil Belajar Matematika Siswa Kelas V Gugus VI Kelekar Kabupaten Muara Enim - Susilawati, Susilawati; Khoirowati, Khoirowati; Suroyo, Suroyo (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is motivated by the not yet optimal learning of mathematics in elementary schools, this can be seen from the low learning outcomes of mathematics. This study aims to: 1) To analyze the differences in mathematics learning outcomes for fifth grade elementary school students using the PBL learning model and conventional models, 2) to analyze the differences in mathematics learning outcomes for 5th grade elementary school students who have high critical thinking skills and those with low critical thinking skills, 3) To analyze the effect of the interaction between the PBL learning model and critical thinking skills on the mathematics learning outcomes of 5th grade elementary school students, 4) to analyze the differences in fifth grade elementary school mathematics learning outcomes for students who have high critical thinking skills between those using the PBL model and conventional models, 5 ) To analyze the differences in mathematics learning outcomes for fifth grade elementary school students who have low thinking skills between those using the PBL model and the conventional model. This type of research is quantitative with a quasi-experimental method. The population is class V students in cluster 6, Muara Enim Regency. The sampling technique is cluster random sampling. The sample taken is 40 students consisting of two classes, namely the experimental class (Class V SDN 3 Kelekar) and the control class (class V SDN 1 Kelekar) data were collected by means of learning outcomes tests and critical thinking skills instruments. The analysis technique uses the Independent Sample T Difference Test, two-way ANOVA technique with a significance level of 0.05. The results showed a significance value of 0.015 <0.05 so it can be concluded that 1) There are differences in learning outcomes for fifth grade elementary school students using the PBL learning model and conventional models, 2) There are differences in math learning outcomes for fifth grade elementary school students who have high critical thinking skills. with low critical thinking, 3) There is an interaction effect between PBL learning models and critical thinking skills on mathematics learning outcomes in fifth grade elementary school, 4) There are differences in mathematics learning outcomes for fifth grade elementary school students who have high critical thinking skills between those using PBL and conventional models. , 5) There are differences in mathematics learning outcomes for fifth grade elementary school students who have low thinking skills between those using the PBL model and the conventional model.